Increasing Time in Therapeutic Range of Tacrolimus in the First Year Predicts Better Outcomes in Living-Donor Kidney Transplantation - Song, Turun; Yin, Saifu; Jiang, Yamei; Huang, Zhongli; Liu, Jinpeng; Wang, Zhiling; Li, Linde; Zeng, Jun; Fan, Yu; Wang, Xianding; Li, Xingxing; Lin, Tao (Frontiers in Immunology, 2019)
Background The aim of the present study is to investigate the impact of time in therapeutic range TTR on long-term outcomes of living kidney transplants. Methods We included 1241 living kidney transplants and randomized them into development and validation cohort with a ratio of 2:1. The tacrolimus TTR percentage was calculated by linear interpolation with target range (5-10 ng/ml months 0-3, 4-8 ng/ml months 4-12). The optimal TTR cutoff was estimated by the receiver operating characteristic curve analysis on the basis of 12 months acute rejection (AR) in development cohort. Outcomes were analyzed between patients with high TTR and low TTR in the development and validation cohort. TTR was also compared with other tacrolimus measures. Results The optimal TTR cutoff value was 78%. In the development cohort, patients with TTR>78% had a significantly higher rejection- and infection-free survival. TTR<78% was an independent risk factor for AR (OR:2.97, 95%CI:1.82-4.84) and infection (OR:1.55, 95%CI:1.08-2.22). Patient and graft survival were significantly higher in those with TTR>78%, and TTR<78% was associated with graft loss (OR:3.2, 95%CI:1.38-7.42) and patient death (OR:6.54, 95%CI:1.34-31.77). These findings were confirmed in the validation cohort. Furthermore, we divided all included patients into high and low TTR group. TTR was more strongly associated with patient and graft survival than mean level, standard deviation and intrapatient variability (IPV). Conclusions Increasing TTR of tacrolimus in the first year was associated with improved long-term outcomes in living kidney transplants, and TTR may be a novel valuable strategy to monitor tacrolimus exposure.